Analysis And Evaluation Of The Performance Of A Low-Pressure Boiler Feed Pump Induction Motor Based On Temperature Increase - Muhammad Aisyur Rifky Maulanaa; Royb Fatkhur Rizal (International Journal of Health Engineering and Technology, 2026)
The induction motor in the Low Pressure Boiler Feed Pump (LP BFP) system plays a crucial role in ensuring the smooth operation of the power generation process at the combined cycle power plant. An increase in motor temperature is a key indicator for evaluating performance and detecting potential operational issues at an early stage. This study aims to analyze and evaluate the performance of the LP BFP induction motor based on temperature rise and motor vibration conditions at PT PLN Nusantara Power UP Gresik. The research method employs a descriptive quantitative approach through field observations, temperature measurements, vibration analysis, and the collection of motor operational data. The results show that the motor temperature on the Drive End (DE) side is 56.8°C and on the Non-Drive End (NDE) side is 47.6°C, which are still within normal operating limits. However, the vibration analysis results indicate bearing damage with an ALARM status based on ISO 10816-3. Therefore, regular temperature monitoring and preventive maintenance are crucial to maintaining the motor’s operational reliability.